Clinical Presentation And Risk Factors Of Oral Squamous Cell Carcinoma Patients In Karachi, A Multicenter Cross-Sectional Study - Abid, Maryam; Zahid, Atiqa; Kumar, Vishal; Bai, Anchal; Abubakar, Aimen; Altaf, Anum (Journal of Neonatal Surgery, 2025)
Background: Oral Squamous Cell Carcinoma (OSCC) is the most common malignancy of the oral cavity and ranks among the leading cancers in South Asia. Pakistan carries a high burden due to widespread use of smokeless tobacco, areca nut and delayed presentation. Objectives: To evaluate the clinical presentation and associated risk factors of OSCC patients presenting at Darul Sehat Hospital, Jinnah Postgraduate Medical Centre (JPMC), and Dow International Dental College (DIDC), Karachi. Methods: A multicenter cross-sectional study (January–June 2025) of histopathologically confirmed OSCC patients (N = 366). Demographic, exposure and clinical data were collected via structured questionnaire and record review. Data were analyzed with SPSS v22; descriptive statistics, chi-square tests, and multivariable logistic regression were applied; significance set at p < 0.05. Results: Mean age was 52.4 ± 12.3 years; 71% were male. Most common sites were buccal mucosa (39.9%) and tongue (30.1%). Major risk factor were smokeless tobacco (63.4%), areca nut (52.7%), cigarette smoking (37.2%), and poor oral hygiene (69.4%). Late-stage presentation (III–IV) occurred in 68% of cases. Smokeless tobacco use was strongly associated with buccal mucosa lesions (p<0.001), cigarette smoking with tongue lesions (p=0.02), and low education with late-stage disease (p<0.001). Multivariable regression showed smokeless tobacco (aOR=1.9, p=0.01), areca nut (aOR=1.8, p=0.03), and low education (aOR=2.2, p=0.001) significantly predicted late-stage disease. Conclusion: High prevalence of smokeless tobacco/areca nut use and frequent late-stage presentation highlight the need for targeted prevention and early-detection programs in Karachi